Publishing National Cultural Periodicals in Lithuania: A Reflection of Cultural Functions in 2000–2015 - Urbanavičiūtė-Globienė, Asta (Knygotyra, 2022)
Cultural periodicals, as a specific part of the field of culture and publishing, can be studied in several directions: 1) by analysing the conceptual aspect of cultural periodicals, i.e., realisation of their cultural functions; 2) by taking into account the general models of publishing periodicals; 3) by analysing other aspects of publishing that are specific to cultural periodicals only, for example, the specific features of funding. This article analyses how the cultural functions of national periodicals were realised in the context of the virtualisation of cultural periodicals in the period under research (in 2000–2015). (In this article, the virtualisation of cultural publications is understood as the transfer of cultural periodicals (magazines, newspapers) into the virtual space or their creation in that space (blogs, portals, social networks)). Cultural periodicals as a part of the cultural field were relevant in the period under research: 1. It is relevant to transmit and preserve cultural information (in this case, the communicative link between the cultural message and the cultural space and the lasting value of cultural texts); 2. To form new addressees to receive the cultural message (each publication brings together its own audience and thus complements the overall cultural field, thus attracting new readers by disseminating cultural information); 3. To actualise the message being sent through more diverse channels (the importance of internationality), to expand the possibilities of accessibility and availability of cultural texts; changes in the media (social networks, portals, websites) have created a broader, more modern and more diverse cultural field of communication. Between the years 2000 and 2015, media change gradually turned into a necessity. First of all, it was undertaken as a way to reach more readers. Due to the specific content, cultural publications were moderate in their approach to the changes in form during the period under analysis: to maintain a high-quality printed version was a priority to them. On the other hand, cultural publications, although not always willingly, began to recognize the importance of the Internet and to consider it as a platform for disseminating cultural information. This aspect became an important turning point in the publishing of cultural periodicals.